Urban regeneration to enhance sustainable mobility: The 2018 Call for proposals of the Emilia-Romagna Region - Pellicelli, Gloria; Rossetti, Silvia; Caselli, Barbara; Zazzi, Michele (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Urban regeneration processes represent an opportunity to pursue a sustainable city model. From a sustainable city perspective, the contribution to the redesign of public space and mobility infrastructures and to the improvement of pedestrian and cycle accessibility to local public services is undoubtedly significant. Within this framework, the Italian Region of Emilia-Romagna, promoted an Urban regeneration Call in 2018 to which cities submitted project proposals concerning the redevelopment of both architectural emergencies and public open spaces, paying particular attention to sustainable mobility issues. About 100 proposals have been submitted and several municipalities received funding. This paper analyses in particular the proposals submitted by the provincial capital cities, through a comparative approach, focusing on mobility, accessibility improvements and open space redevelopment. The aim is to highlight similarities and differences in order to identify some common guiding principles for enhancing sustainable urban mobility.